Sección geológica del Pacífico al Atlántico a través de Costa Rica - Rivier Sutter, Francois (2011)
A geological profile through Costa Rica, from the Osa Peninsula, on the pacific coast, to the Punta Cahuita on the atlantic coast, permits to rebuild the geological history of the two main basins, in which acumulated more than 5000 meters of tertiary sediments, forming one regressive megasecuence: the Térraba basin on the SW flank of the Talamanca mountain range and the Talamanca basin on the NE flank of the same mountain range. Each basin shows a distinct compressive tectonic style: the Térraba basin presents scales and inverse fauts, with subsidence of the backward part of the basin, while the Talamanca basin presents a gravitative land slide to the sedimentary cover, with important overlaps on the foot of the mountain range, in the coastal plain.